THE ROLE OF THE ACHIEVEMENT TEACHER IN IMPROVING STUDENTS' CHARACTERS THROUGH THE HABIT OF READING THE QUR'AN AT MTS NURUL HIDAYAH - Hendrik, Hendrik (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The role of the teacher of moral beliefs is a primary part because the teacher is someone who directly interacts with students at school. Therefore, the role of teachers must be maximized to improve students' morals in accordance with the existing habits and curriculum which are supported by the teacher's competence and qualifications as an educator. The purpose of this research is to (1) Describe the role of moral aqidah teachers as educators in improving students' morals through the habit of reading the Al-Qur'an, (2) Describe the influence of the habit of reading the Al-Qur'an implemented by moral aqidah teachers on changes in students' morals . The research method used is a qualitative approach as a research procedure that produces descriptive data in the form of words. With this type of field research. Meanwhile, data collection uses observation, interviews. For the analysis method, the descriptive reflective thinking method is used. In presenting data by drawing a conclusion. The results of this research indicate that the role of the moral aqidah teacher in improving the morals of students at MTs Nurul Hidayah has been implemented, namely through the habitual activity of reading the Al-Qur'an, where the role of the moral aqidah teacher is to act as an educator, the role of the moral aqidah teacher as an educator is to be a role model. for students and the role of a teacher is to teach students about good morals because teachers play an important role not only in the classroom but outside the classroom to create students who have morals. karimah because considering that in today's era, there is a lack of morals towards a teacher.